2023
DOI: 10.1021/acsnano.2c12356
|View full text |Cite
|
Sign up to set email alerts
|

Attenuating Uncontrolled Inflammation by Radical Trapping Chiral Polymer Micelles

Abstract: As a clinical unmet need, uncontrolled inflammation is characterized by the crosstalk between oxidative stress and an inflammatory response. Ferroptotic cell death plays an essential role in uncontrolled inflammation. Hence ferroptosis inhibition is capable of managing hyper-inflammation, but the small molecular inhibitors show poor residence in cell membranes. The plasma membrane is the major site of lipid peroxidation that is the key event of ferroptosis. To address such a challenge, chiral radical trapping … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…reported that by wrapping CuV 2 O 6 nanobelt with GO nanosheets using a combination of hydrothermal treatment and ultrasonication, while the resultant composite displays a higher specific capacity of 30%–46% versus pristine CuV 2 O 6 and it has a slight capacity fading of 99.3% after 3000 cycles. [ 52 ] Such difference in specific capacity is due to the thin CuV 2 O 6 /GO layer formation, leading to a shorter distance for Zn 2+ ions diffusion. Due to the poor contact point between the V oxide nanoparticles and conductive graphene layers, the specific capacity of the ZIBs is normally compromised.…”
Section: Zinc‐ion Batteriesmentioning
confidence: 99%
See 1 more Smart Citation
“…reported that by wrapping CuV 2 O 6 nanobelt with GO nanosheets using a combination of hydrothermal treatment and ultrasonication, while the resultant composite displays a higher specific capacity of 30%–46% versus pristine CuV 2 O 6 and it has a slight capacity fading of 99.3% after 3000 cycles. [ 52 ] Such difference in specific capacity is due to the thin CuV 2 O 6 /GO layer formation, leading to a shorter distance for Zn 2+ ions diffusion. Due to the poor contact point between the V oxide nanoparticles and conductive graphene layers, the specific capacity of the ZIBs is normally compromised.…”
Section: Zinc‐ion Batteriesmentioning
confidence: 99%
“…[ 11–19,26–30 ] b) Ragone plots of recent development of GBMs in LIB, ZIB, ZAB, and ZnI 2 B. [ 19,30–59 ] c) Radar chart comparison of LIBs versus advanced rechargeable ZBBs. [ 42,50,58,59 ]…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, vanadium oxides are abundant and can provide high capacity, which are considered promising cathode candidates for AZIBs. A series of vanadium oxides have been explored as cathodes for AZIBs in previous studies, such as NH 4 V 4 O 10 , [ 6 ] Na 0.5 K 0.5 VO, [ 7 ] V 2 O 5 ·nH 2 O, [ 8 ] Na 1.1 V 3 O 7.9 , [ 9 ] CuV 2 O 6 , [ 10 ] δ ‐Ni 0.25 V 2 O 5 ·nH 2 O, [ 11 ] Na 3 V 2 (PO 4 ) 3 , [ 12 ] NaCa 0.6 V 6 O 16 ·3H 2 O, [ 13 ] V 5 O 12 ·6H 2 O, [ 14 ] etc. Among them, VO is composed of VO 6 octahedron and VO 5 triangular bipyramid, and its layered structure makes the intercalation and deintercalation of Zn 2+ relatively easy.…”
Section: Introductionmentioning
confidence: 99%
“…[ 11,13 ] However, commonly used zinc salts such as zinc sulfate (ZnSO 4 ) and zinc trifluoromethanesulfonic [Zn(OTf) 2 ] have low solubility in hydrogel solutions. [ 14,15 ] Another effective strategy to improve the mobility of Zn 2+ at low water content is to modify the hydrogel skeleton for limiting anion transportation and increasing the amount of free Zn 2+ , [ 16 ] then the cation transference number will be significantly increased and the system becomes a single‐ion‐conducting electrolyte (SICE) with a transference number close to 1. [ 17,18 ] As the anion migration is greatly hindered, the concentration gradient and polarization that may cause the dendrite growth could be effectively suppressed, leading to the stable depositing/stripping processes on the zinc metal surface, [ 16,18,19 ] which is essential to improve the cycle performance of ZIBs.…”
Section: Introductionmentioning
confidence: 99%